The Role of Customer Satisfaction in Mediating the Influence of the 5P Marketing Mix on Customer Loyalty of Jenius Bank BTPN in Yogyakarta - Agustin Hermawati; Arthur Sitaniapessy; Maya Maria (Yayasan Riset dan Pengembangan Intelektual, 2024)
Research Aims: This study aims to evaluate the influence 5P marketing mix on customer loyalty, with customer satisfaction as a mediating variable, specifically for Jenius Bank BTPN customers in Yogyakarta. Design/methodology/approach: This research adopts a quantitative descriptive. Data were collected through a questionnaire Jenius customers. A total of 160 questionnaires were distributed, but only 140 valid responses were used due to 22 respondents not meeting the predefined criteria. Research Findings: The findings indicate that, directly, the product, price, and people variables have a positive and significant impact on customer loyalty, while place and promotion do not. However, in the indirect relationship, product, price, and promotion positively and significantly influence customer loyalty when mediated by customer satisfaction, whereas place and people do not show a significant indirect effect. Theoretical Contribution/Originality: It highlights the influence of product, price, and promotion on satisfaction and loyalty, providing strategic insights for Jenius Bank BTPN.